Formação continuada de professores e escola de tempo integral: a experiência do município de São José de Ribamar - MA - Almeida, Erika Christianne Sousa Pereira de (2016)
The present study deals with the Continuing Education of teachers who work in a School of Integral Time of the Municipal Network of Teaching of São José de Ribamar-MA. Its main objective is to analyze the continuing education offered to the teachers who work in the school full time. To do so, we used the qualitative approach, using instruments and techniques of bibliographic research, documentary analysis, observation, semi-structured interview and questionnaire application for profile characterization. The research was carried out in a school that lives the full-time experience, and had the participation of 11 subjects: coordinator, teachers and Assistant Secretary of Pedagogical Management. The questions addressed aspects about the theoretical and methodological orientations, full - time conception, and the repercussions of continuing education for full - time school performance, from 2008 to 2012 in the field. The theoretical basis for Continuing Teacher Training was the contribution of: Nóvoa (1992, 1995 and 1999), Alarcão (2011), Contreras (2002), Tardif (1999, 2002, 2005, 2014), Gatti (2008), Pimenta (1994, 1997, 2000 and 2002), Kuenzer (1999), Paulo Freire (1996), Libâneo (2000), Freitas (2002), Romanelli (2003), Cabral Neto and Macêdo ), Romanowski and Martins (2010); In the discussion about full-time schooling and integral education, we sought to establish a foundation in Cavaliere (2007, 2009), Moll (2008), Paro (2009), Mauricio (2009), Menezes (2009), Coelho e Hora Among other authors. It was concluded, based on the study, that the continued formation of teachers is still a complex subject to be discussed in the Brazilian scenario, characterizing itself as a hegemonic formative model of the tradition, based on the technical, utilitarian rationalism that limits the teacher's Context of the classroom. When it comes to the context of the full-time school researched, it is evident that, although the municipality has advanced towards a differentiated school not only in structural and pedagogical aspects, especially in the initial years of its implantation, As a training / qualification to develop methodologies, without direct relation with the challenges and needs of the full-time school, so that the offered one has not offered subsidies for a better foundation and performance of the teachers.